Makna Implikatur Akibat Pelanggaran Maksim Kerja Sama Dalam Komik Kimi Ni Todoke Karya Shiina Karuho (Kajian Pragmatik) - Bulan Dwigitta Prativi, Ni Made; Yuliani Giri, Ni Luh Kade; Andry Anita Dewi, Ni Made (Humanis, 2016)
This research entitled “Implicature meaning which happened because of violates the maxims of conversation in the cooperative principle in Kimi Ni Todoke’s Manga by Shiina Karuho”.The theories used for analyzing are  the cooperative principle theory by Grice and speech acts (illocutionary acts) theory by Searle. This research aims to find out the type of maxim of conversation which got violated in Kimi Ni Todoke by Shiina Karuho and also the implied meaning of it. Based on the analysis that has been done, there are 21 dialogues which violates maxim of conversation, there are 6 dialogues for maxim of quantity, 5 dialogues for maxim of quality, 6 dialogues for maxim of relation, 4 dialogues for maxim of manner and 4 dialogues for violates two maxims at the same time. There are also five types meaning of the implicatures based on illocutionary acts, such as assertives, directives, expressives, commisives and declarations.